1996
DOI: 10.1021/jp953381p
|View full text |Cite
|
Sign up to set email alerts
|

Basis Set Effects in Density Functional Calculations on the Metal−Ligand and Metal−Metal Bonds of Cr(CO)5−CO and (CO)5Mn−Mn(CO)5

Abstract: The basis set superposition error (BSSE) for the Cr(CO) 5 -CO and (CO) 5 Mn-Mn(CO) 5 bonds is calculated for a large variety of STO basis sets. All investigated metal basis sets, being at least TZ for 3d and DZ for 4s are adequate. Ligand basis sets of TZD quality or better are required in order to have a low BSSE (6-8 kJ/mol or less) for both the metal-ligand and the metal-metal bond. When the ligand s, p basis set is of double-quality, the BSSE is significant for the metal-ligand bond (16-22 kJ/mol depending… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
136
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 132 publications
(154 citation statements)
references
References 51 publications
18
136
0
Order By: Relevance
“…These basis sets are given in Ref. 36, where also basis set superposition errors for these basis sets in the Cr͑CO͒ 6 and Mn 2 ͑CO͒ 10 complexes have been investigated. Comparing the SR ZORA calculations we conclude from Table V that the results of the frozen core calculations compare very well with our largest calculations, the all electron ͑ae͒ calculations.…”
Section: Resultsmentioning
confidence: 99%
“…These basis sets are given in Ref. 36, where also basis set superposition errors for these basis sets in the Cr͑CO͒ 6 and Mn 2 ͑CO͒ 10 complexes have been investigated. Comparing the SR ZORA calculations we conclude from Table V that the results of the frozen core calculations compare very well with our largest calculations, the all electron ͑ae͒ calculations.…”
Section: Resultsmentioning
confidence: 99%
“…For Ni-(CO) 4 , we used the geometry given in ref 69 with a Ni-C distance of 1.838 Å and a C-O distance of 1.141 Å. For Mn 2 -(CO) 10 , we assumed, as usual, 70 a D 4d symmetry, in which the two sets of equatorial CO's are in a staggered configuration with respect to each other. Three different geometries were used as the results appeared to be strongly geometry dependent.…”
Section: Technical Details Of the Calculationmentioning
confidence: 99%
“…It has been shown that the basis set error of such a ''triple '' basis set for the first bond dissociation energy of Cr͑CO͒ 6 is only a few hundredths of an eV. 30 We have tested the effect of adding f functions to the basis set by doing scalar relativistic calculations with CO at the preferred adsorption sites on Ni, Pd, and Pt. The adsorption energy was affected less than 0.1 eV, and therefore we have found it reasonable to remove the f functions from the basis sets.…”
Section: Computational Detailsmentioning
confidence: 99%